The Mathematical Literacy Task Using the Context of the Traditional Games “Engklek” and “Congklak” - Caswita; Nurain Suryadinata; Siti Mutmainah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
The low level of mathematical literacy among Indonesian students remains a significant challenge, as evidenced by PISA and national assessment results. Although ethnomathematics has been widely recognized as a promising approach to contextualize mathematics learning, studies that specifically develop mathematical literacy tasks based on traditional games and examine their validity, practicality, and effectiveness are still limited. In particular, the integration of traditional games such as